A 3D Osteoblast In Vitro Model for the Evaluation of Biomedical Materials. (28th December 2015) - Restle, Luciana; Costa-Silva, Daniela; Lourenço, Emanuelle Stellet; Bachinski, Rober Freitas; Batista, Ana Carolina; Linhares, Adriana Brandão Ribeiro; Alves, Gutemberg Gomes
Abstract : Biomedical materials for bone therapy are usually assessed for their biocompatibility and safety employing animal models or in vitro monolayer cell culture assays. However, alternative in vitro models may offer controlled conditions closer to physiological responses and reduce animal testing. In this work, we developed a 3D spheroidal cell culture with potential to evaluate simultaneously material-cell and cell-cell interactions. Different cell densities of murine MC3T3-E1 preosteoblasts or human primary osteoblasts (HOb) were used to determine the ideal procedure of spheroidal cultures and their adequacy to material testing. Cells were seeded on 96-well plates coated with agar and incubated in agitation from 1 to 7 days. Aggregate morphology was qualitatively evaluated considering the shape, size, repeatability, handling, and stability of spheroids. Higher cell densities induced more stable spheroids, and handling was considered appropriate starting from 2 × 10 4 cells. Confocal microscopy and Scanning Electron Microscopy indicate that most cells within the aggregate core are viable. Exposure to positive controls has shown a dose dependent cell death as measured by XTT assay. Aggregates were stable and presented good viability when employed on standardized testing of metallic and polymer-based biomaterials. Therefore, osteoblast spheroids may provide a promising tool for material screening and biocompatibility testing.